(untitled) (International Journal of Engineering and Computer Science, 2017)
With recent increase in uses of internet and development of web technologies, proportion of web content in Hindi is increasing at a lightning impetus. These particulars can play a vital role for researchers and computer science engineers in devising systems and real-world application for government organisation and private sector which could ease their decision making process. In this paper, we present a modus operandi to perform lexical analysis on Devanagari Hindi language. This was done by building a dictionary containing Hindi words using few information retrieval techniques and implementing some error recovery strategies to recover from lexical errors (if occurred). We achieved an accuracy of approximately 88% while performing Lexical analysis on different Hindi words. Main advantage of our work is, entire processing of the Lexical analysis phase can be completed in offline mode (i.e. without any usage of internet).